Localized Traps Limited Recombination in Lead Bromide Perovskites. Issue 12 (8th February 2019) - Fu, Jianhui; Jamaludin, Nur Fadilah; Wu, Bo; Li, Mingjie; Solanki, Ankur; Ng, Yan Fong; Mhaisalkar, Subodh; Huan, Cheng Hon Alfred; Sum, Tze Chien
Abstract: Traps exert an omnipotent influence over the performance of halide perovskite optoelectronic devices. A clear understanding of the origin and nature of the traps in halide perovskites is the key to controlling them and realizing optimal devices. Herein, the role of localized traps on the optical properties of lead bromide perovskite films is investigated. In the low‐temperature orthorhombic phase of CH3 NH3 PbBr3 perovskite, band‐edge carrier dynamics exhibit a power‐law decay due to the presence of structural‐disorder‐induced localized traps, which has a depth of ≈40 meV. The continuous distribution of these localized traps gives rise to a broad sub‐band‐gap emission that becomes more prominent in thicker films with a larger trap density. The presence of this emission only from the hybrid organic–inorganic perovskites points to the vital role of organic dipoles in localized trap states formation. This study explicates the nature of these localized traps as well as their nontrivial role in carrier recombination kinetics, which is of fundamental importance in perovskites optoelectronics. Abstract : The photophysics and nature of localized traps and their role on the optical properties of lead bromide perovskite films are investigated using optical spectroscopy and theoretical modeling. A clear understanding of the origin and nature of localized traps has important ramifications for perovskite light harvesting and emitting applications, as well as the design of new perovskites.